Respuesta :

Answer:

the equation is true only if c=6 and d=2.

Step-by-step explanation:

We have the following expression:

[tex]\sqrt[3]{162x^{c}y^{5}} = 3x^{2}y\sqrt[3]{6y^{d}}[/tex]

Elevating to the power of three:

[tex]162x^{c}y^{5}=27x^{6}y^{3}(6y^{d})[/tex]

Simplifying:

→ [tex]162x^{c}y^{5}=162x^{6}y^{3}y^{d}[/tex]

→ [tex]x^{c}y^{5}=x^{6}y^{3}y^{d}[/tex]

→ [tex]x^{c}y^{5}=x^{6}y^{d+3}[/tex]

By comparing the two expression, we can say that:

[tex]c=6[/tex]

[tex]d+3 = 5[/tex] → [tex]d=2[/tex]

Therefore, the equation is true only if c=6 and d=2.

Answer:

c = 6 d = 2

on edge

ACCESS MORE